Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 38 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Puma yagouaroundi (É.Geoffroy Saint-Hilaire, 1803)", "Geometry POLYGON((-114.81 13.63,-114.81 31.15,-84.87 31.15,-84.87 13.63,-114.81 13.63))", "HasGeospatialIssue is false", "HasCoordinate is true", "BasisOfRecord is Specimen" ] } The dataset includes 38 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002705-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences